2007
DOI: 10.1152/ajpregu.00117.2007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of maternal high-fat feeding on hypothalamic leptin sensitivity and diet-induced obesity in the offspring

Abstract: Epidemiological and animal studies suggest that the alteration of hormonal and metabolic environment during fetal and neonatal development can contribute to development of metabolic syndrome in adulthood. In this paper, we investigated the impact of maternal high-fat (HF) diet on hypothalamic leptin sensitivity and body weight gain of offspring. Adult Wistar female rats received a HF or a control normal-fat (C) diet for 6 wk before gestation until the end of the suckling period. After weaning, pups received ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
137
3
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 50 publications
16
137
3
9
Order By: Relevance
“…After delivery, HF dams lost relatively more weight than did C dams, mainly during the second half of the lactation Adaptation to lactation in a model of obesity O Zagoory-Sharon et al period, and then the body weight became identical in the two groups at the end of the weaning period'. 53 Overall, these patterns of weight differences are very similar to those described in the current study, in which OLETF rats were much heavier than LETO controls as NP and on Lac1, although this difference dramatically decreased on Lac15 and 22 (Table 1). This similarity suggests that the pattern of OLETF adaptation to lactation may reflect their general hyperphagia-obesity phenotype, rather than, or possibly, in addition to, its specific CCK-1 mutant status.…”
Section: Discussionsupporting
confidence: 86%
“…After delivery, HF dams lost relatively more weight than did C dams, mainly during the second half of the lactation Adaptation to lactation in a model of obesity O Zagoory-Sharon et al period, and then the body weight became identical in the two groups at the end of the weaning period'. 53 Overall, these patterns of weight differences are very similar to those described in the current study, in which OLETF rats were much heavier than LETO controls as NP and on Lac1, although this difference dramatically decreased on Lac15 and 22 (Table 1). This similarity suggests that the pattern of OLETF adaptation to lactation may reflect their general hyperphagia-obesity phenotype, rather than, or possibly, in addition to, its specific CCK-1 mutant status.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies in rodents have assessed influences of maternal high-energy diets using only a short time window, generally less than 14 days prior to mating or only during gestation and/or lactation, and have generally failed to achieve obesity in the dam [16,19,20,[24][25][26]. A few, using a prolonged feeding period to induce obesity [17,27,28], have generally switched from a high-energy diet to a control diet postdelivery [28], potentially inducing changes of the milk composition [29]. Since lactation may be a critical period for neonates in the programming of obesity, these protocols may affect the offspring phenotype [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our laboratories and others have shown that a maternal diet rich in animal fat during gestation and lactation leads to the development of an offspring phenotype with characteristics of the metabolic syndrome even when offspring are reared on a normal diet [16][17][18][19][20]. However, these dietary manipulations were made only during the short period of gestation and lactation and rodents fed a diet rich in fat alone are generally resistant to the development of obesity [16].…”
mentioning
confidence: 99%
“…The proximal occlusion cuff (O-cuff) constricts the tail artery while the distal VPR cuff measures the change in tail artery volume when blood flow resumes as the O-cuff deflates. This system has been validated in a number of studies [14,15,17] . These measurements were performed in a room maintained at 31 °C so as to ensure adequate blood flow through the tail to improve the signal at the VPR transducer.…”
Section: Experimental Designmentioning
confidence: 99%
“…In recent years, a new technique for measuring blood pressure in conscious rats using a volume pressure recording system has been validated in a number of studies [14,15] . Longterm oral administration of (±)doxazosin (8 mg/kg for 12 weeks) in the rat was also reported in a study by Yono et al [16] .…”
Section: Introductionmentioning
confidence: 99%